A. V. Schleicher. Colloquial Yoruba: The Complete Course for Beginners. New York and London: Routledge, 2008. 295 pp. - Taiwo Oluwaseun Ehineni (Yoruba Studies Review)
Book review of A. V. Schleicher's Colloquial Yoruba: The Complete Course for Beginners. New York and London: Routledge, 2008. 295 pp.